2019 IEEE 58th Conference on Decision and Control (CDC) 2019
DOI: 10.1109/cdc40024.2019.9029407
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Nonblockingness in Bounded Petri Nets With a Semi-Structural Approach

Abstract: This paper proposes a semi-structural approach to verify the nonblockingness of a Petri net. We provide an algorithm to construct a novel structure, called minimax basis reachability graph (minimax-BRG): it provides an abstract description of the reachability set of a net while preserving all information needed to test if the net is blocking. We prove that a bounded deadlock-free Petri net is nonblocking if and only if its minimax-BRG is unobstructed, which can be verified by solving a set of integer linear pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…On the other hand, in our previous work [33] we show that the standard BRG cannot be directly used to solve the NB-V problem due to the possible presence of livelocks and deadlocks. In particular, livelocks describe an undesirable non-dead repetitive behavior such that the system is bound to evolve along a particular subset of its reachability space.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…On the other hand, in our previous work [33] we show that the standard BRG cannot be directly used to solve the NB-V problem due to the possible presence of livelocks and deadlocks. In particular, livelocks describe an undesirable non-dead repetitive behavior such that the system is bound to evolve along a particular subset of its reachability space.…”
Section: Introductionmentioning
confidence: 77%
“…However, the set of markings that form a livelock is usually hard to characterize and is not encoded in the classical BRG of the system. As a countermeasure, preliminary results are presented in [33] to show how it is possible to tailor the BRG to detect livelocks. In more detail, a structure named the expanded BRG is proposed, which expands the BRG so that all markings in R(N, M 0 ) reached by firing a sequence of transitions ending with an explicit transition are included.…”
Section: Introductionmentioning
confidence: 99%
“…Given a plant net, in general there exist several valid basis partitions, each of which leads to a different BRG. According to Example 1 presented in [10], a BRG constructed with a randomly selected basis partition may not encode all information needed to test if a plant is non-blocking. The reason lies in the fact that in a BRG there may exist some livelocks among a set of non-basis markings; thus, the blocking behavior of the plant net cannot be detected by checking the structure of the BRG.…”
Section: Non-blockingness Verification Using Conflict-increase Brgsmentioning
confidence: 99%
“…Although the BRG-based techniques have been proved to be operative and efficient, in [10], [11] we have shown that a conventional BRG is in general not applicable to tackle the non-blockingness verification problem. The reason is that in a BRG there may exists some livelocks among a set of non-basis markings.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation